Tingkat Anxiety (Kecemasan) Atlet Karate Sentra Pembinaan Olahragawan Berbakat Nasional (Spobnas) Gorontalo - Riska Ayu Febrianti; Hariadi Said; Sulasikin Sahdi Kadir (Gorontalo State University, 2026)
This study aims to determine and describe the anxiety levels of karate athletes at the National Talented Athlete Development Center (SPOBNAS) Gorontalo before competing. Anxiety is a psychological factor that can affect an athlete's performance in competitive sports, especially in karate, which demands physical, technical, tactical, and mental readiness. This study used a descriptive qualitative approach to gain an in-depth understanding of the psychological conditions of athletes before competition. The subjects were 5 active karate athletes at SPOBNAS Gorontalo. Data collection was conducted through the Sport Competitive Anxiety Test (SCAT) questionnaire to determine initial anxiety levels, followed by interviews to explore the athletes' experiences and feelings in more detail. Interviews also aimed to strengthen the research results to make them more comprehensive. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results showed that most athletes had moderate anxiety levels, with 60% in the moderate category and 40% in the low category. These findings indicate that athletes' anxiety before competition is still within normal limits and is not dominated by high anxiety. Therefore, athletes are advised to participate in structured mental training to maintain psychological stability and improve their readiness for competition.